Effectiveness of Leaves Extract Fractions of Archidendron jiringa (Jack) I.C Nielsen Against Microbes - Oom Komala; Sri Wardatun; Lia Puspita Sari (Universitas Jenderal Soedirman, 2019)
Archidendron jiringa(Jack) I.C Nielsen) contains a lot of essential oils, saponins, alkaloids, terpenoids, steroids, tannins, glycosides, and flavonoids. Flavonoid is a secondary metabolite compound in a plant as antimicrobial. This study aims to determine the antimicrobial activity of fractions of ethanol 96%, n-hexan, ethyl acetate, and ethanol-water leaves extractand determine levels of favonoids. A. jiringaleaves extract were tested against Streptococus mutans, Pseudomonas aeruginosa, and Candida albicans. The research using agar disc diffusion technique for antimicrobial activity and colorimetric method to know the total of flavonoid. Chloramphenicol and ketoconazole were used as a reference standard. The result of this study shows fractions of ethanol 96%, n-hexane, ethyl acetate, and ethanol-water A. jiringaleaves extract can inhibit microbial growth of S. mutans, P. aeruginosa, and C. albicans.Total of flavonoids on the extract respectively are 1.13%, 0.494%, 2.337%, and 0.549%. determined with complementary colorimetry to each leaf extract fractionA. jiringawith aluminum chloride method. Absorption spectrum measurement using a spectrophotometer. The higher percent of flavonoids would cause greater bacteriainhibitory zone but only 0.090 for pearson correlation value. Conclusions ethyl acetate leaves extract most effective inhibit microbial growth from the other fractions.